Exploring Gender Learning Styles Preferences at Junior High School - Etika Dewi Kusumaningtyas; Anastasya Shelfy Anggraeani; Regita Ika Wulandari; Muhammad Ali Mustofa (Journalistics: Journal of English Teaching and Applied Linguistics, 2024)
Personal characteristic of learning by each student can be analyze as a basic way to distinguish its learning styles. There are factors establish learning style such as environment, sociological, physiological and psychological. This research purposed to explore gender preferences of leaning style at Junior High School. the majority preferences of learning style of male are kinesthetic with 69%, followed by 35% of auditory and 28% of visual. While 72% female students preferred visual, 65% voted for auditory and 31% choose kinesthetic. the result of this research shows this research found that most of female preferred visual learning style and majority of male preferred kinesthetic.